2016
DOI: 10.1177/1040638715625729
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pecorum

Abstract: Chlamydial abortion in small ruminants is usually associated with Chlamydia abortus infection. Although Chlamydia pecorum has been detected in aborted ruminants and epidemiological data suggests that C. pecorum is abortigenic in these species, published descriptions of lesions in fetuses are lacking. This work describes fetoplacental lesions in a caprine abortion with C. pecorum infection, and further supports the abortigenic role of C. pecorum in ruminants. A 16-month-old Boer goat aborted twin fetuses at ~13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…The veterinary pathogen C. pecorum is linked to a range of diseases in cattle, sheep, pigs and goats, including polyarthritis, encephalomyelitis and conjunctivitis [20]. Rare cases of C. pecorum –associated abortion in ruminants have also been reported [21]. While this pathogen has been long recognized as a major threat to the survival of Australia's iconic native marsupial, the koala [22], recent molecular and serologic studies have shown other wildlife globally may harbour strains of this pathogen.…”
Section: Old Chlamydia Species New Infectionsmentioning
confidence: 99%
“…The veterinary pathogen C. pecorum is linked to a range of diseases in cattle, sheep, pigs and goats, including polyarthritis, encephalomyelitis and conjunctivitis [20]. Rare cases of C. pecorum –associated abortion in ruminants have also been reported [21]. While this pathogen has been long recognized as a major threat to the survival of Australia's iconic native marsupial, the koala [22], recent molecular and serologic studies have shown other wildlife globally may harbour strains of this pathogen.…”
Section: Old Chlamydia Species New Infectionsmentioning
confidence: 99%
“…The mentioned study confirmed the presence of C. abortus in La Pampa Province, not far from Mendoza Province, the location of the present case. Sporadic abortions in goats from Uruguay were associated with C. pecorum (Giannitti et al 2016). However, to the best of our knowledge, there have been no reports of ovine or caprine enzootic abortion associated with C. abortus in Argentina.…”
Section: Discussionmentioning
confidence: 84%
“…© 2019 The Authors Veterinary Medicine and Science Published by John Wiley & Sons Ltd Veterinary Medicine and Science (2019), 5, pp. 162-167reported in Uruguay(Giannitti et al 2016), Chile (OIE 2012 and Argentina (this report). Humans are at highest risk during and immediately after abortion or parturition as large numbers of this organism are released to the environment with the fetal fluids(Seth-Smith et al 2017).…”
mentioning
confidence: 68%
See 2 more Smart Citations